Howell’s cytological grading of breast carcinomas - comparison with histological grading and its association with lymph node metastasis - Dr. Koshalya Rajendran; Dr. Muthu Sudalaimuthu; Dr. Shivashekar Ganapathy (Tropical Journal of Pathology and Microbiology, 2018)
Background: Determining histological grade of breast carcinomas before mastectomy is necessary to decide about neo-adjuvant chemotherapy. Grade obtained from fine needle aspiration cytology samples will help in such situations particularly when core needle biopsy is not done routinely as inresource-poor setups. Methods for doing such gradingare still under study. We performedgrading of breast carcinomas in Fine Needle Aspiration smearsby Howell’s method and correlatedthe resultswith modified Bloom-Richardson histological grade in mastectomy specimens. For the first time, we also studied the prognostic significance of Howell’s grade by studying its association with lymph node metastasis.Materials and methods: Fifty cases of Invasive carcinoma- no special type of breast in which both mastectomy and fine needle aspiration cytology were done between 2013 and 2015 were included in our study. Howell’s grading was done in Papanicolaou, Haematoxylin & eosin and May-Grunwald Giemsa stained cytology smears and correlated with modified Bloom Richardson histological grading in mastectomy specimens.Results: The two methods had same grade in 34 cases (68%) and a kappa agreement value of 0.505. They showed a good positive correlation (Spearman correlation coefficient 0.732) and significant association (chi-square test, p-0.0001). 12 cases were under-graded and four were over-graded. Lymph node metastasis significantly increased with increase in Howell’s cytological grade (p-0.018).Conclusion: Howell’s cytological grading is a simple method to grade breast carcinomas before mastectomy. This method has a good concordance with histological grading.The strong association with lymph node metastasis indicates the prognostic significance of this grading method.